Peran Koperasi Simpan Pinjam Ub. Amanah Dalam Mengembangkan Potensi Ekonomi Anggota Dan Masyarakat - Tri Yunita Nabila; Ripho Delzy Perkasa (Peneliti.net, 2023)
Cooperative development is very important because it contributes to the development of community financial potential. This study aims to determine the role of UB.Amanah savings and loans in developing the economic activities of members and the community. This research is a descriptive-analytic research. Data collection techniques used include interviews and observations, as well as literature review from various journal sources related to the topic. Based on the results of the research analysis, the UB.Amanah cooperative can play an important role in developing the financial welfare of members and the community by providing financial and capital support without certain criteria.